Community Perception Towards Bandung Zoological Garden Activities (A Case Study of Corporate Social Responsibility at the Bandung Zoological Garden) - Adli, Amas Sultan Dinul; Wisesa, Anggara (Journal of Business and Management, 2021)
Corporate social responsibility is an important part of building good relationships with thesurrounding community. This study aims to determine the causes of negative perceptions from thecommunity towards the Bandung Zoological Garden, especially in RW 07 and RW 08. This studyused a qualitative approach through the Yin case study method (Yin: 2013). This case study was toexplain cases coherently and clearly with 3 analyzes, namely pattern matching, making explanations,and time series analysis. The results of this study indicated that corporate responsibility affectedcorporate reputation, corporate image, and social legitimacy. This had led to a negative perception ofthe Bandung Zoological Garden due to the inadequacy of the Bandung Zoological Garden in makingcorporate responsibility programs and policies that tend to harm the surrounding community.Keywords: Corporate Responsibility, Corporate Reputation, Corporate Image, Social Legitimacy,Community Perception